2001
DOI: 10.1021/es0110067
|View full text |Cite
|
Sign up to set email alerts
|

Further Biogeochemical Characterization of a Trichloroethene-Contaminated Fractured Dolomite Aquifer:  Electron Source and Microbial Communities Involved in Reductive Dechlorination

Abstract: A recent article presented geochemical and microbial evidence establishing metabolic adaptation to and in-situ reductive dechlorination of trichloroethene (TCE) in a fractured dolomite aquifer. This study was designed to further explore site conditions and microbial populations and to explain previously reported enhancement of reductive dechlorination by the addition of pulverized dolomite to laboratory microcosms. A survey of groundwater geochemical parameters (chlorinated ethenes, ethene, H2, CH4, DIC, DOC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…The TAN groundwater community had many similarities with those of other dechlorinating sites. Although not as dominant as they were at TAN, Clostridia were also present in an aquifer where TCE was being intrinsically degraded predominantly to cis-DCE at the Lawrence Livermore National Laboratory (50), in an aquifer undergoing intrinsic natural attenuation of hydrocarbons and chlorinated alkanes at Wurtsmith Air Force Base (14), and in a predominantly Fe(III)-reducing TCE-contaminated aquifer (36,85). All three of these other sites also had members of candidate division OP11, and the two of the three sites where complete declorination was observed had green nonsulfur Bacteria (the group to which Dehalococcoides is most similar).…”
Section: Discussionmentioning
confidence: 99%
“…The TAN groundwater community had many similarities with those of other dechlorinating sites. Although not as dominant as they were at TAN, Clostridia were also present in an aquifer where TCE was being intrinsically degraded predominantly to cis-DCE at the Lawrence Livermore National Laboratory (50), in an aquifer undergoing intrinsic natural attenuation of hydrocarbons and chlorinated alkanes at Wurtsmith Air Force Base (14), and in a predominantly Fe(III)-reducing TCE-contaminated aquifer (36,85). All three of these other sites also had members of candidate division OP11, and the two of the three sites where complete declorination was observed had green nonsulfur Bacteria (the group to which Dehalococcoides is most similar).…”
Section: Discussionmentioning
confidence: 99%
“…Among the motivations for this study was a desire to understand the mechanism by which naturally occurring microbial populations at a coal tar-contaminated field site (2,20,23,33) adapt to introduced organic substrates. Previously it has been shown that Cg1-like plasmids, involved in horizontal transfer of naphthalene catabolic genes between bacteria at the study site, are homologous to the archetypal naphthalene catabolic plasmid pDTG1 from P. putida NCIB 9816-4 (despite some variability in overall plasmid sizes [e.g., pDTG1, 81 kb; and pCg1, 86 kb {52}]).…”
Section: Discussionmentioning
confidence: 99%
“…Groundwater was obtained from well 36 in October 2001 and used for biodegradation assays. To prevent contact between water samples and air (25,78), the receiving glass canning jars (2 liters for water samples and 0.5 liter for sediments) were flushed on site with nitrogen gas and, after they were filled, sealed without air bubbles. Freshly gathered, oxygen-free subsurface material (depth, 5 m) from an area adjacent to well 36 was obtained with a commercially operated Geoprobe hydraulic coring machine.…”
Section: Methodsmentioning
confidence: 99%
“…The sediment was immersed in anaerobic groundwater before it was sealed in a canning jar with no headspace air. The groundwater and sediments were placed on ice and maintained at 4°C until they were dispensed into serum bottles with an N 2 headspace containing a trace of H 2 in an anaerobic hood (Coy Laboratory Products, Grass Lake, MI) within 2 days, as previously described (25,78). Triplicate sterile 125-ml serum bottles received 72 ml of well 36 groundwater plus 10% (wt/vol) well 36 sediment from 2 m below the water table.…”
Section: Methodsmentioning
confidence: 99%